Univerzální kontrolní a měřící stanice - Brýdl, Adam (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Předmětem této diplomové práce je návrh a konstrukce poloautomatické kontrolní a měřicí stanice. Stanice je určena pro testování přítomnosti a měření správné polohy světlovodů a těsnění v konektoru. Stanice obsahuje přípravek na testování zaslepení konektorů. Návrh a konstrukce poloautomatické kontrolní a měřicí stanice je nutný s využitím více druhů snímačů a posuvných lineárních os řízených servopohony. Zadání diplomové práce je řešeno ve spolupráci se společností Mechatronic Design & Solutions s. r. o. v Brně.

The task of this thesis is the design and construction of semi-automatic control and measuring station. The station is designed for testing the presence and measurement of the correct position of light guides and seals in the connector. Station contains a tool for testing the blinding of connectors. The design and construction of a semi-automatic control and measuring station is necessary using several types of sensors and sliding linear axes controlled by servo drives. The assignment of the thesis is solved in cooperation with the company Mechatronic Design & Solutions s.r.o. in Brno.
Universal Inspection and Measuring Station
Keywords: světlovod; těsnění; tělo konektoru; sonda; modul; inlet; ESD zóna; IO-Link; light pipe; seal; housing; probe; module; inlet; ESD zone; IO-Link